2019
DOI: 10.1016/j.chom.2018.12.008
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Balances the Fitness Costs and Benefits of Disrupting the Host Cell Actin Cytoskeleton Early after Mucosal Transmission

Abstract: SUMMARY: HIV-1 primarily infects T lymphocytes and uses these motile cells as migratory vehicles for effective dissemination in the host. Paradoxically, the virus at the same time disrupts multiple cellular processes underlying lymphocyte motility, seemingly counterproductive to rapid systemic infection. Here we show by intravital microscopy in humanized mice that perturbation of the actin-cytoskeleton via the lentiviral protein Nef, and not changes to chemokine receptor expression or function, is the dominant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
42
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(46 citation statements)
references
References 53 publications
3
42
0
1
Order By: Relevance
“…It has been shown, however, that CD4 + T cells latently infected with HIV contain high levels of viral integration in the Mrtfa and Mrtfb loci, implying that disruption of the MRTF pathway enables infected cells to elude the immune system (Maldarelli et al, 2014). Furthermore, the HIV virulence factor Nef, which disrupts cytoskeletal polarity, was recently found to enhance the survival of infected cells in an immunocompetent mouse model (Usmani et al, 2019). Therefore, defining the genetic and molecular bases of mechanosurveillance will likely illuminate cellular immunity against not only cancer but also infectious disease.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown, however, that CD4 + T cells latently infected with HIV contain high levels of viral integration in the Mrtfa and Mrtfb loci, implying that disruption of the MRTF pathway enables infected cells to elude the immune system (Maldarelli et al, 2014). Furthermore, the HIV virulence factor Nef, which disrupts cytoskeletal polarity, was recently found to enhance the survival of infected cells in an immunocompetent mouse model (Usmani et al, 2019). Therefore, defining the genetic and molecular bases of mechanosurveillance will likely illuminate cellular immunity against not only cancer but also infectious disease.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the population and velocity of eosinophils in different organs and their changes in the normal and ovalbumin sensitization state can be seen with IVM ( 45 ). Also, IVM was applied to images to analyze how HIV infection changes T-cell motility and migration patterns by disrupting host-cell cytoskeletons ( 46 ) and how pathogen-specific T cells interact with intracellular parasite-infected cells ( 47 ). In addition, in vivo imaging of tissues with IVM discovered the novel tissue-specific immune responses, including the studies that viewed glycoengineered antibodies potentiate the B-cell depletion by macrophages in the liver ( 48 ) and supported other discoveries on liver immunology in various diseases states with IVM ( 49 ).…”
Section: Introductionmentioning
confidence: 99%
“…Interfering with leukocyte recirculation in chronically infected animals did not impact viremia ( Murooka et al., 2012 ), suggesting that HIV is actively carried into peripheral tissues and blood by migratory cells predominantly during the early stages of infection. More recently, we showed that enhanced migratory capacity of infected T cells, by disrupting Nef-mediated dysregulation of the actin cytoskeleton, accelerated systemic viral dissemination shortly after vaginal transmission, further implicating HIV-infected lymphocytes as motile vehicles for efficient viral spread ( Usmani et al, 2019 ). Thus, HIV can hijack physiological immune surveillance, cellular trafficking and intercellular communication in order to evade immune recognition and reach large numbers of susceptible T cells in lymphoid organs ( Fackler et al., 2014 ; Murooka and Mempel, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Another outstanding question is how DCs, in the absence of productive infection, restrain motile T cells to promote stable DC:T cell conjugates to facilitate viral transfer. We and others have utilized 3D collagen model systems to better characterize the dynamic on-off kinetics between infected and uninfected cells and have described key aspects of cell-cell contact behaviors that impact viral dissemination kinetics and pathogenesis ( Lopez et al., 2019 ; Symeonides et al., 2015 ; Usmani et al, 2019 ). Herein, we addressed whether HIV-captured DCs retain their ability to exit the genital mucosae, enter the lymphatic vessels, and migrate toward LN-homing chemo-attractants and whether they can restrain motile T cells for long enough to permit viral transfer in the absence of cognate antigen recognition.…”
Section: Introductionmentioning
confidence: 99%